Characterization of the human thyroid epigenome. Issue 2 (November 2017) - Siu, Celia; Wiseman, Sam; Gakkhar, Sitanshu; Heravi-Moussavi, Alireza; Bilenky, Misha; Carles, Annaick; Sierocinski, Thomas; Tam, Angela; Zhao, Eric; Kasaian, Katayoon; Moore, Richard A; Mungall, Andrew J; et al.
Abstract : The thyroid gland, necessary for normal human growth and development, functions as an essential regulator of metabolism by the production and secretion of appropriate levels of thyroid hormone. However, assessment of abnormal thyroid function may be challenging suggesting a more fundamental understanding of normal function is needed. One way to characterize normal gland function is to study the epigenome and resulting transcriptome within its constituent cells. This study generates the first published reference epigenomes for human thyroid from four individuals using ChIP-seq and RNA-seq. We profiled six histone modifications (H3K4me1, H3K4me3, H3K27ac, H3K36me3, H3K9me3, H3K27me3), identified chromatin states using a hidden Markov model, produced a novel quantitative metric for model selection and established epigenomic maps of 19 chromatin states. We found that epigenetic features characterizing promoters and transcription elongation tend to be more consistent than regions characterizing enhancers or Polycomb-repressed regions and that epigenetically active genes consistent across all epigenomes tend to have higher expression than those not marked as epigenetically active in all epigenomes. We also identified a set of 18 genes epigenetically active and consistently expressed in the thyroid that are likely highly relevant to thyroid function. Altogether, these epigenomes represent a powerful resource to develop a deeper understanding of the underlying molecular biology of thyroid function and provide contextual information of thyroid and human epigenomic data for comparison and integration into future studies.